Seafloor images from a mining trial at the Belgian (GSR) contract area in the Clarion Clipperton Zone during the MANGAN 2021 (IP21) expedition - Iason-Zois Gazis; Karl Heger; Jochen Mohrmann; Henko de Stigter; Matthias Haeckel; Jens Greinert (PANGAEA, 2025)
Raw seafloor time-series images with an Ocean Imaging Systems (OIS) DSC 24,000 Digital Still Camera at ca. 1 m above the seafloor during the mining trial at the Belgian (GSR) contract area in the Clarion Clipperton Zone.